Health risk of cyanotoxins in Lake Victoria and household drinking water for riparian communities along Nyanza Gulf - Otoigo, Lilian (My University, 2020)
Cyanotoxins are produced by cyanobacteria which are single-celled algae that thrive in warm and nutrient rich water bodies including lakes. There are different kinds of cyanotoxins and microcystin is the most common. Microcystin mostly affects the liver. Epidemiological studies in China and Serbia have shown an association between cyanotoxins and occurrence of Primary Liver Cancer. Cyanobacteria have been reported in Lake Victoria, which is an important source of drinking water for the riparian communities, thus posing a danger to human health. However, the health risk from exposure to toxic cyanobacteria in the Nyanza Gulf water remains unknown. The purpose of this study was to assess the health risk of toxic cyanobacteria to the riparian communities in the Nyanza Gulf. In a longitudinal study adopting survey and experimental design, 127 samples were collected monthly from both households and six beaches over six months. Cyanobacterial levels were determined using an enzyme assay method (PP2A). Different methods of household water treatment were compared. Two-way ANOVA was done to determine statistical significance of microcystins levels. 84% of water samples contained microcystins. Concentration of microcystins was 3.44g/L which is over the WHO limit of 1g/L. There was no variation between beaches and water treatment (ANOVA: F=0.97, p=0.47). Filtration proved to be the most efficient method of water treatment. The health risk factor of cyanotoxins in drinking water is 3.86. There is a health risk posed by cyanotoxins to the residents of the Nyanza Gulf who use the lake water for drinking since is over the WHO limit. This information provides an insight into the quality of Lake Victoria water for drinking. The study recommends development of cyanobacteria removal methods as well as sensitizing the riparian communities on the health risk of cyanotoxins in drinking water.
Keywords: Cyanotoxins; Microcystin; Health risk; TDI; PP2A; Water treatment